California Democratic Council Statewide Convention at Hacienda Inn - Watkins, Howard::::::::: (1982)
Close up of U.S. Senator Ted Kennedy speaking; Fresno Mayor Dan Whitehurst looking at Senator "Convention Banner: "We the people action for the '80's"